Kepekaan Eschericia coli Patogen yang Diisolasi dari Babi Penderita Kolibasilosis terhadap Antibiotik di Kecamatan Kerambitan dan Tebanan Kabupaten Tabanan, Bali - Aditya Nugraha; NK. Besung; Hapsari Mahatmi (Udayana University, 2013)
This study aims to determine the sensitivity pattern of E. coli isolated from pigs with colibacillosis to antibiotics. The total of 21 fecal samples was collected from pigs with white scour at the District of Kerambitan and Tabanan, the Regency of Tabanan, Bali. The isolation and identification of pathogenic E coli used Sheep Blood Agar medium, and serotype grouping of those bacteria was designated through agglutination test using serum’s antibody Polyvalent 1-5 and 6-11. The pathogenic E. coli found was then examined it`s own resistance to streptomycin, sulfamethoxazole, gentamicin, cefotaxime, and chloramphenicol according to Kirby Bouer method. The result showed that the isolates of E. coli polyvalent 1-5 were resistant to streptomycin and chloramphenicol, whereas that of polyvalent 6-11 was resistant to sulfamethoxazole, gentamicin, streptomycin and chloramphenicol.